Chassis durability and comfort trade-off at early stage of project by virtual proving ground simulation. Issue 6 (3rd June 2022) - Gao, Hanwei; Jézéquel, Louis; Cabrol, Eric; Vitry, Bernard
Abstract : The simulation of vehicle chassis system is widely deployed at the early stage of a new car development project in order to verify if the technical specifications such as durability and comfort of current design are fulfilled. However, the numerical validations of specifications are usually carried out independently by project teams, which may fail to converge the final design at downstream phase of projects. This paper proposes an early stage multi-objective optimisation method which is able to search a set of best trade-offs between durability and comfort before the deployment of the chassis parameters. Virtual proving ground simulation is applied as a uniformed numerical validation platform, following the same process as in physical experiments, including global and local damage calculation, transfer function estimation and other comfort criteria. By realising the design of experiments on front and rear axles' global curves and key components in a deployable design space, the Pareto front can be obtained in several optimisation iterations. An application case on an example project shows the method succeeds in revealing the general trends between these two chassis specifications with acceptable simulation costs. The data-mining methods further demonstrate the design preferences and orientations of each group in the simulation database.